A novel facial image recognition method based on perceptual hash using quintet triple binary pattern - Tuncer, Turker; Dogan, Sengul; Abdar, Moloud; Plawiak, Pawel (Springer, 2020)
Image classification (categorization) can be considered as one of the most breathtaking domains of contemporary research. Indeed, people cannot hide their faces and related lineaments since it is highly needed for daily communications. Therefore, face recognition is extensively used in biometric applications for security and personnel attendance control. In this study, a novel face recognition method based on perceptual hash is presented. The proposed perceptual hash is utilized for preprocessing and feature extraction phases. Discrete Wavelet Transform (DWT) and a novel graph based binary pattern, called quintet triple binary pattern (QTBP), are used. Meanwhile, the K-Nearest Neighbors (KNN) and Support Vector Machine (SVM) algorithms are employed for classification task. The proposed face recognition method is tested on five well-known face datasets: AT&T, Face94, CIE, AR and LFW. Our proposed method achieved 100.0% classification accuracy for the AT&T, Face94 and CIE datasets, 99.4% for AR dataset and 97.1% classification accuracy for the LFW dataset. The time cost of the proposed method isO(nlogn). The obtained results and comparisons distinctly indicate that our proposed has a very good classification capability with short execution time.
Keywords: Face recognition; Quintet triple binary pattern; Perceptual hash; Machine learning; Biometrics